Rehabilitation of a tibial plateau fracture within an elite female mountainbiker. A case report - Hynd, J. (Journal of Science and Cycling, 2015)
Tibial plateau fractures present a challenging problem for elite athletes and medical personnel, with many athletes failing to return to previous sporting levels post fracture (Johansson etal, 1992). An elite professional female endurance mountainbiker (Age: 32, Height: 1.58m, Body Mass: 51kg) presented 3 weeks post injury with a severe left tibial plateau fracture, caused by a fall when skiing. An orthopaedic surgeon in France inserted two screw fixations from lateral to medial condyles within the left tibia. X-rays and CT scans revealed a large degree of damage to the superolateral surface of the tibial plateau. The surgeon described an unusual and potentially career threatening injury. The athlete was advised to completely rest for a minimum of 10 weeks. This created uncertainty and concern for future career status and sponsorship. Prior to injury, a 12 week training period in France involved intensive skiing and running on steep alpine roads. During this time the athlete experienced progressive knee pain, perhaps caused by a change in knee load relative to high volume cycling. According to Bargfeldt etal (2011) high impact training loads may cause microcracks within the tibia. Furthermore, female athletes are at particular risk due to amenorrhea, a reduction in oestrogen levels and resultant reduction in bone mass.